Differential CXCR4 expression on hematopoietic progenitor cells versus stem cells directs homing and engraftment - Sydney Felker; Archana Shrestha; Jeff Bailey; Devin M Pillis; Dylan Siniard; Punam Malik (JCI Insight, 2022)
Gene therapy involves a substantial loss of hematopoietic stem and progenitor cells (HSPC) during processing and homing. Intra-BM (i.b.m.) transplantation can reduce homing losses, but prior studies have not yielded promising results. We studied the mechanisms involved in homing and engraftment of i.b.m. transplanted and i.v. transplanted genetically modified (GM) human HSPC. We found that i.b.m. HSPC transplantation improved engraftment of hematopoietic progenitor cells (HPC) but not of long-term repopulating hematopoietic stem cells (HSC). Mechanistically, HPC expressed higher functional levels of CXCR4 than HSC, conferring them a retention and homing advantage when transplanted i.b.m. Removing HPC and transplanting an HSC-enriched population i.b.m. significantly increased long-term engraftment over i.v. transplantation. Transient upregulation of CXCR4 on GM HSC-enriched cells, using a noncytotoxic portion of viral protein R (VPR) fused to CXCR4 delivered as a protein in lentiviral particles, resulted in higher homing and long-term engraftment of GM HSC transplanted either i.v. or i.b.m. compared with standard i.v. transplants. Overall, we show a mechanism for why i.b.m. transplants do not significantly improve long-term engraftment over i.v. transplants. I.b.m. transplantation becomes relevant when an HSC-enriched population is delivered. Alternatively, CXCR4 expression on HSC, when transiently increased using a protein delivery method, improves homing and engraftment specifically of GM HSC.